2018
DOI: 10.1002/jcp.27108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microRNA‐26a on vascular endothelial cell injury caused by lower extremity ischemia–reperfusion injury through the AMPK pathway by targeting PFKFB3

Abstract: Vascular endothelial cell (VEC) dysfunction plays an important role in the ischemia-reperfusion injury (IRI)-related diseases, and microRNAs (miRNAs) are key factors during this process. We conducted this study to investigate whether miRNA-26a (miR-26a) has effect on the IRI-induced VEC injury via the AMPK pathway by targeting 6-phosphofructo-2-kinase-fructose-2,6-biphosphatase 3 (PFKFB3). IRI rat models were successfully constructed by an abdominal incision. Additionally, the cultured VECs were further treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Wu et al reported that miR-26a can inhibit PFKFB3 in a targeted manner, thereby reducing VEC injury caused by lower-extremity ischemia-reperfusion. After miR-26a overexpression or silencing of PFKFB3 expression in VEC, it was reported that CEC count and expression levels of TM and vWF all were markedly decreased in vascular tissues of mice with IRI [28]. In the present study, we found that the control group had lower CEC, TM, and vWF levels than in the other groups.…”
Section: Discussionsupporting
confidence: 55%
“…Wu et al reported that miR-26a can inhibit PFKFB3 in a targeted manner, thereby reducing VEC injury caused by lower-extremity ischemia-reperfusion. After miR-26a overexpression or silencing of PFKFB3 expression in VEC, it was reported that CEC count and expression levels of TM and vWF all were markedly decreased in vascular tissues of mice with IRI [28]. In the present study, we found that the control group had lower CEC, TM, and vWF levels than in the other groups.…”
Section: Discussionsupporting
confidence: 55%
“…Further, EV-mediated delivery of miR-126 improved endothelial barrier function in an in vitro model [60]. Functionally, miR-126 has been shown to protect endothelial cells against H/R mediated damage, while miR-26a protects endothelial cells against ischemia-reperfusion injury [62,63]. Finally, miR-126 inhibits expression of vascular cell adhesion molecule 1 (VCAM-1), which functions to bind leukocytes and promotes inflammation [64].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…YAP is an important effector of the Hippo pathway, and plays important roles in regulating cell proliferation, migration, and differentiation (Feng et al, 2016; Huang et al, 2016). The role of YAP in organ development, tumorigenesis and metastasis, and regenerative medicine has received increasing attention (Zhu et al, 2018; Moya and Halder, 2019; Wu et al, 2019). YAP, which is a transcriptional coactivator, is distributed in both the nucleus and cytoplasm, and its localization affects its function.…”
Section: Introductionmentioning
confidence: 99%